Responsabilidad del Estado frente al derecho a la seguridad social de migrantes venezolanos y la necesidad de regular el flujo migratorio en el Ecuador. - Yaruscuán Cadena, Cynthia Rebeca (2023)
Ecuador is a highly committed nation, due to its internal policy, in providing asylum, refuge and protection to migrants in a situation of displacement by zoo or voluntary human mobility; Consequently, Ecuador has a high responsibility at the national and international level regarding the recognition of human rights in favor of migrants, for this reason, our country has ratified several international instruments on asylum and refuge and has incorporated into the Constitution various principles and guarantees tending to ensure the exercise of the rights of migrants. Despite the commitment of the Ecuadorian State to generate a defense fence, the necessary and necessary public protection policies have not yet been used; that is to say, it has not been possible to fully safeguard the full exercise of the rights of migrants, regarding all those rights inherent to the workplace, such as the right to work, to social security, to job stability, etc.; This problem, in large part, is due to the lack of regularization of the migratory flow that has made it impossible to carry out an exact control of the migrants who have entered our territory, thus allowing the irregular hiring of people to be carried out, which In search of an economic source that allows them to survive, they have agreed to provide their services for a salary lower than that provided by law and in their great majority without access to social security. The Constitution of the Republic, several international treaties and conventions for the protection of labor rights such as the Convention on Social Security (1952) ratified by the Ecuadorian State on October 25, 1974 and the Convention on equal treatment (Social Security) (1962) ratified by the Ecuadorian State on March 9, 1970, agree that social security is a worker's right and its purpose is to guarantee health, medical assistance in case of maternity, illness, accident and disability and protection in case of disability, unemployment and old age; Non-affiliation with social security violates access to these benefits and gives rise to labor exploitation, unequal working conditions between nationals and foreigners, irregular and regular migrants, and also generates an economic impact on the Ecuadorian Institute of Social Security IESS due to the lack of contribution of migrants who occupy jobs in Ecuadorian territory irregularly. 5 In accordance with the provisions of previous paragraphs, the purpose of this research project is to reveal the violation of the right to social security faced by migrants of Venezuelan nationality in Ecuadorian territory when they are employed in different workplaces by various types of hiring. and even irregularly, without having affiliation to social security and consequently deprived of access to benefits from said affiliation; In addition, determine the responsibility of the State in the face of this violation and the need to regulate the migratory flow in Ecuador to minimize and/or avoid prolonging this problem that has affected several families of migrants. The present investigation was developed under a descriptive methodology that focuses on the analysis and description of the characteristics of the problem addressed, which allowed determining the responsibility of the State against the violation of the rights to social security of Venezuelan migrants, among the types The research used is the bibliographical research, field research and legal research that allowed us to analyze the national and international regulations that support the proposed hypothesis and the application of surveys to Venezuelan migrants as a data collection technique, which were processed and analyzed to finally make the conclusions and recommendations. KEYWORDS: Social Security, Violation of Rights, Migration, Migrants, Control